057 Para-herpetic SUNCT syndrome. Issue 6 (27th May 2022) - Sim, Nicholas Keyi; ,; Ying, Li; Mowafi, Walied
Abstract : Pre and post-herpetic SUNCT syndrome is a rare but previously reported complication of herpes zoster reactivation. We report a case of a zoster associated SUNCT syndrome developing at the same time as reactivation. A 79-year-old gentleman was referred to Neurology for refractory right sided facial pain. 7 months prior to presentation he had developed shingles in the right upper face around his forehead area, which was managed by his GP. At the same time, he developed daily attacks of sharp stabbing pain behind his eye, up to 5 a day, lasting up to 5 minutes each. This was associated with injection and lacrimation of the affected eye. The attacks can be triggered by touch, such as a shower. Neurological examination was unremarkable except for allodynia in the right V1 distribution. Plain MRI scan showed cortical atrophy only. He had a good response to lamotrigine. nchlasim@doctors.org.uk